Evropsko povezovanje interesnih skupin in javne politike v Sloveniji - Fink-Hafner, Danica (Teorija in praksa, 2000)
The paper focuses on one of several aspects of the Europeanisation of Central Eastern European politics by looking at the Europeanising role of interest groups in (re)shaping national policy-making processes due to influences of European Union actors, as well as European integration processes. Candidate-states' civil societies, crossing national borders with international networking, are developing into important factors of changing policy processes and policy contents within candidate-states. Research in Slovenia supports the hypothesis that European interest groups (both Euro-groups and kindred interest groups from EU member-states) have a significant impact on Europeanisation of Slovenian politics by transferring their knowledge, expertise and know-how to Slovenian interest groups as well as by supporting Slovenian interest groups in agenda-setting and all other keystages in Slovenian policy-making and policy implementation.
Keywords: mednarodni politični odnosi; interesne skupine; European Union; Evropska unija; Slovenia; Slovenija; članstvo; večnacionalna država; politično upravljanje; politični interesi